2013
DOI: 10.1136/bmjopen-2012-002312
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting versus short-acting methylphenidate for paediatric ADHD: a systematic review and meta-analysis of comparative efficacy

Abstract: ObjectiveTo synthesise existing knowledge of the efficacy and safety of long-acting versus short-acting methylphenidate for paediatric attention deficit hyperactivity disorder (ADHD).DesignSystematic review and meta-analysis.Data sourcesElectronic literature search of CENTRAL, MEDLINE, PreMEDLINE, CINAHL, EMBASE, PsychINFO, Scopus and Web of Science for articles published in the English language between 1950 and 2012. Reference lists of included studies were checked for additional studies.Study selectionRandom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
1
26
0
2
Order By: Relevance
“…In the current study, we will, therefore, focus on those functions that are known to be often compromised in ADHD and have been sufficiently studied in the context of MPH effects to conduct a meta-regression analysis. Although not previously addressed in meta-analyses regarding the effects of MPH on executive functioning, previous research has shown that medication naivety (Schwartz & Correll, 2014), dosage (Tannock et al 1995;Konrad et al 2004Konrad et al , 2005 and MPH formulation (Punja et al 2013) are additional potential moderators of the effects of stimulants. Shiels et al 2009;Luman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we will, therefore, focus on those functions that are known to be often compromised in ADHD and have been sufficiently studied in the context of MPH effects to conduct a meta-regression analysis. Although not previously addressed in meta-analyses regarding the effects of MPH on executive functioning, previous research has shown that medication naivety (Schwartz & Correll, 2014), dosage (Tannock et al 1995;Konrad et al 2004Konrad et al , 2005 and MPH formulation (Punja et al 2013) are additional potential moderators of the effects of stimulants. Shiels et al 2009;Luman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the cocaine-like discriminative-stimulus effects of three cocaine-like DUIs, cocaine, its analogWIN35,428, and methylphenidate (an FDA-approved medication for treatment of attention deficit hyperactivity disorders, ADHD) (19). Each of these compounds has been shown to preferentially bind the outward facing conformation of the DAT (13, 20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we observed similar responses to treatment while there were substantially more side effects in patients using OROS-MPH. The findings of a recent review, which considers studies comparing IR-and ER-MPH formulations, indicated that long-acting forms of MPH had a modest effect on the severity of inattention/overactivity and hyperactivity/impulsivity according to parent reports, whereas the short-acting MPH was preferred according to teacher reports for hyperactivity [17]. On the other hand, similar adverse events were observed with IR-and ER-MPH formulations in this study [17].…”
Section: Discussionmentioning
confidence: 49%